2014
DOI: 10.1172/jci77511
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin-binding protein 5 exocytosis regulation: differential role in endothelial cells and platelets

Abstract: C o m m e n t a r y 4 2 3 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Interestingly, STXBP5 has also been shown to differentially regulate exocytosis in endothelial cells and platelets [44, 45]. While STXBP5 facilitates granule release from platelets, it inhibits secretion from the WPB of endothelial cells [46]. Recently, Torisu et al observed another novel type of regulation of VWF release through an observation that WPBs are often in close proximity of autophagosomes [47].…”
Section: Regulation Of Vwf Protein Secretionmentioning
confidence: 99%
“…Interestingly, STXBP5 has also been shown to differentially regulate exocytosis in endothelial cells and platelets [44, 45]. While STXBP5 facilitates granule release from platelets, it inhibits secretion from the WPB of endothelial cells [46]. Recently, Torisu et al observed another novel type of regulation of VWF release through an observation that WPBs are often in close proximity of autophagosomes [47].…”
Section: Regulation Of Vwf Protein Secretionmentioning
confidence: 99%
“…4, 8, 9 More recently, we and others found STXBP5 is a novel regulator of platelet granule exocytosis and thrombosis. 1012 …”
Section: Introductionmentioning
confidence: 99%
“…58,[73][74][75][76][77][78] These loci may modulate VWF plasma levels either by involvement in intracellular trafficking and exocytosis of VWF (e.g., STX2 and STXBP5 genes) or through cellular uptake and clearance of VWF from plasma (e.g., STAB2, SCARA5, CLEC4M, and LRP1). 78,79 Further ex vivo gene expression and in vivo mouse studies of CLEC4M provided additional evidence that a variable number of tandem repeat (VNTR) polymorphisms in CLEC4M gene influence VWF levels in plasma. The CLEC4M protein is a lectin receptor possessing an N-terminal cytoplasmic domain, a transmembrane domain and an extracellular neck region which is highly polymorphic possessing three to nine VNTRs of a conserved 23-aa sequence.…”
Section: Genetic Determinants Outside Vwf Contributing To Variabilitymentioning
confidence: 99%